1990
DOI: 10.1080/02681219080000291
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans—do mycelia matter?

Abstract: Growth of Candida albicans in the mycelial phase is neither necessary for initiation of infection in the kidney of the mouse, following intravenous inoculation, nor for the establishment of chronic renal colonization. However, mycelial formation would appear to be important in the establishment of pelvic lesions with their associated pathological changes. Two mycelia-less mutants, CA-2 and MM2002, in the early stages of infection tended to develop in the glomeruli of the mouse kidney cortex while the wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
3

Year Published

1993
1993
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 13 publications
1
46
0
3
Order By: Relevance
“…While some histological sections of diseased tissues are virtually free from hyphal cells other studies suggest that hyphae are better able to gain a foothold in the primary invasion of a host tissue (Martin et al, 1984;Sobel e t al., 1984). Experiments using animal models and strains that are debilitated in hyphal formation have shown that the yeast cells are undoubtedly pathogenic in their own right (Simonetti & Strippoli, 1973;Shepherd, 1985;Ryley & Ryley, 1990) but equivalent hyphal-competent strains penetrate more deeply into the host tissues (Ryley & Ryley, 1990). From a teleological point of view tip-growing hyphae would seem well adapted for penetration of surfaces such as epithelia and it is with that in mind that we have looked for behavioural adaptations of the germ tube when grown in contact with a surface.…”
Section: Filamentous Growth Of Candida Albicansmentioning
confidence: 99%
“…While some histological sections of diseased tissues are virtually free from hyphal cells other studies suggest that hyphae are better able to gain a foothold in the primary invasion of a host tissue (Martin et al, 1984;Sobel e t al., 1984). Experiments using animal models and strains that are debilitated in hyphal formation have shown that the yeast cells are undoubtedly pathogenic in their own right (Simonetti & Strippoli, 1973;Shepherd, 1985;Ryley & Ryley, 1990) but equivalent hyphal-competent strains penetrate more deeply into the host tissues (Ryley & Ryley, 1990). From a teleological point of view tip-growing hyphae would seem well adapted for penetration of surfaces such as epithelia and it is with that in mind that we have looked for behavioural adaptations of the germ tube when grown in contact with a surface.…”
Section: Filamentous Growth Of Candida Albicansmentioning
confidence: 99%
“…Dimorphic growth, the ability to grow in more than one form, is believed to contribute to the pathogenicity of C. albicans (Corner and Magee, 1997). Mutant strains that are defective in switching between ®lamentous growth and budding growth frequently exhibit reduced virulence (Sobel et al, 1984;Shepherd, 1985;Ryley and Ryley, 1990;Leberer et al, 1997). Recently, a well-de®ned mutant strain with a profound defect in ®lamentous growth was shown to be avirulent after intravenous inoculation of mice (Lo et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…This fungus is a common commensal of the gut, mouth and vagina, but under certain circumstances it can cause both superficial infections, and in the case of immunocompromised patients, serious systemic infections (Odds, 1987). It is thought that both the yeast and hyphal forms of C. albicans can be pathogenic (Kerridge, 1993;Ryley & Ryley, 1990). Investigations concerning C. albicans iron acquisition and uptake have to date been limited.…”
Section: Introductionmentioning
confidence: 99%